A public health evaluation of 13-valent pneumococcal conjugate vaccine impact on adult disease outcomes from a randomized clinical trial in the Netherlands. Issue 38 (10th September 2019) - Gessner, Bradford D.; Jiang, Qin; Van Werkhoven, Cornelis H.; Sings, Heather L.; Webber, Chris; Scott, Daniel; Neuzil, Kathleen M.; O'Brien, Katherine L.; Wunderink, Richard G.; Grobbee, Diederick E.; Bonten, Marc J.M.; Jodar, Luis
Abstract: Background: We conducted a post-hoc analysis of a double blind, randomized, placebo-controlled trial of 13-valent pneumococcal conjugate vaccine (PCV13) among adults aged 65 years or older to assess public health impact. Methods: For all outcomes, we included all randomized subjects, using a modified intention-to-treat (mITT) approach to determine vaccine efficacy (VE), vaccine preventable disease incidence (VPDI) defined as control minus vaccinated group incidence, and numbers needed to vaccinate (NNV) (based on a five-year duration of protection). Results: Results are reported for, in order, clinical, adjudicated (clinical plus radiologic infiltrate determined by committee), pneumococcal, and vaccine-type pneumococcal (VT-Sp) community-acquired pneumonia; invasive pneumococcal disease (IPD) and VT-IPD. VEs (95% CI) for all hospital episodes were 8.1% (−0.6%, 16.1%), 6.7% (−4.1%, 16.3%), 22.2% (2.0%, 38.3%), 37.5% (14.3%, 54.5%), 49.3% (23.2%, 66.5%), and 75.8% (47.6%, 88.8%). VPDIs per 100, 000 person-years of observation (PYOs) were 72, 37, 25, 25, 20, and 15 with NNVs of 277, 535, 816, 798, 1016, and 1342. For clinical CAP, PCV13 was associated with a reduction of 909 (−115, 2013) hospital days per 100, 000 PYOs translating to a reduction over 5 years of one hospital day for every 22 people vaccinated. When comparing at-risk persons (defined by self-report of diabetes, chronic lung disease, or other underlying conditions) to not at-risk persons, VEs were similar or lower, but because baseline incidences were higher the VPDIs were approximately 2–10 times higher and NNVs 50–90% lower. Conclusion: A public health analysis of pneumonia and IPD outcomes in a randomized controlled trial found substantial burden reduction following adult PCV13 immunization implemented in a setting with an ongoing infant PCV7-PCV10 program. VPDIs were higher among at-risk adults. Funding: The original study and the current analysis were funded by Pfizer.